Políticas e práticas do Terceiro Setor na educação brasileira, no contexto de reconfiguração do estado - Lélis, Úrsula Adelaide de (2006)
This work fits in the research line of Public Policies and Education Management of the Program of Postgraduation in Education of the Federal University of Uberlândia. We explore the policies and proceedings of the third sector in Brazilian education, in the process of reconfiguration of the Restricted State, through the study of a municipal and scholastic management program the Champ School Program conducted by public-private entities in a county of Minas Gerais in the 2001-2004 period. Its goal is considering the emergence and strengthening of such entities go over the role of the third sector on the process of absorption of the public space by modern private enterprises, in the context of the creation of the Ample State and the retrenchment of the Restricted State, within the new wealth cycle. Firstly, we analyse the materialization of these policies in the setting of Montes Claros/MG, through the implementation of the Champ School Program . In this stage, we use, as a source for the research, official documentation of the Program and its management indexes instruments for its control and evaluation. Afterwards, we develop a bibliographical survey on the strategy of the political, economical and social intervention that implemented the public-private segment in Brazil: the Neoliberalism. We finish with a survey about the third sector in Brazilian contemporaneity, discussing its aspects, deadlocks and perspectives. The results from this research bear witness the instrumented functionality of the third sector to the process of reconformation of the Restricted State, through the resignification of the concept of citizenship, the conversion of social rights into benefits, the progressive mixture of public and private forces, and the viabilization of a new modality of privatization of the scholastic process: the public purveyance, with public, private and public-private funding, and public-private management, which originate a new form of capitalist reproduction.